Modeling Geoelectric Fields in Ireland and the UK for Space Weather Applications. Issue 2 (5th February 2019) - Campanyà, J.; Gallagher, P. T.; Blake, S. P.; Gibbs, M.; Jackson, D.; Beggan, C. D.; Richardson, G. S.; Hogg, C.
Abstract: Geoelectric fields at the Earth's surface caused by geomagnetic storms have the potential to disrupt and damage ground‐based infrastructure such as electrical power distribution networks, pipelines, and railways. Here we model geoelectric fields in Ireland and the UK during both quiet and active time intervals of geomagnetic conditions using measurements from magnetic observatories and electromagnetic tensor relationships. The analysis focused on (1) defining periods of the magnetic field variations that are largely affected by the geomagnetic storms, between 30 and 30, 000 s; (2) constraining the electromagnetic tensor relationships that defines the Earth's response to magnetic field variations; (3) implementing and validating two approaches for modeling geoelectric fields based on measurements from magnetic observatories and local and interstation electromagnetic transfer functions; and (4) estimating uncertainties when modeling geoelectric fields. The use of interstation tensor relationships allowed us to differentiate between regional and local geomagnetic sources. We found coherence values of 0.5–0.95, signal‐to‐noise ratio of 1–15 dB, normalized root‐mean‐square values of 0.8–3.4, and root‐mean‐square values of 0.7–84 mV/km. Within these ranges of values, sites in close proximity (<100 km) to a magnetic observatory and not affected by local storms will provide the most accurate results, while sites located at further distances and affected by spatially localized features of the storm will be less accurate. These methods enable us to more accurately model geomagnetically induced currents, and their associated uncertainties, in the British and Irish power networks. Key Points: A new method for estimating geoelectric fields based on geomagnetic field time series and electromagnetic geophysical parameters is reported The method successfully reproduces electric and magnetic fields measured during both quiet and active time intervals in Ireland and the UK Modeled geoelectric fields accuracy depends on the distance to the closest magnetic observatory, and on the influence of local storms